The association of TNF-alpha secretion and mtDNA copy number in CD14+ monocytes of patients with obesity and CHD - Tolstik, Taisiya V.; Kirichenko, Tatiana V.; Markin, Alexander M.; Bogatyreva, Anastasia I.; Markina, Yuliya V.; Kiseleva, Diana G.; Shaposhnikova, Nataliya N.; Starodubova, Antonina V.; Orekhov, Alexander N. (Frontiers in Molecular Biosciences, 2024)
Mitochondrial dysfunction may be one of the causes of inflammatory activation of monocytes and macrophages, which leads to excessive secretion of inflammatory mediators and the development of chronic inflammation.The study was aimed to evaluate the secretion of inflammatory cytokine tumor necrosis factorα (TNF-α) in the primary culture of monocytes, and to analyze its relationship with the number of mitochondrial DNA (mtDNA) copies in the blood of patients with coronary heart disease (CHD) and obesity. Material and methods: 108 patients with obesity and concomitant CHD and a control group of 25 participants were included in the study. CD14+ monocytes were isolated by a standard method in a ficoll-urographin gradient, followed by separation using magnetic particles. The number of mtDNA copies was estimated using qPCR. Results: It was demonstrated that the number of mtDNA copies was significantly increased in groups of patients with CHD and obesity + CHD in comparison with control group. mtDNA copy number positively correlated with basal and LPS-stimulated TNF-α secretion, the most significant correlation was found in the group of patients with CHD and obesity. Conclusion: Thus, the change in mtDNA copy number in CD14+ monocytes which indicates the presence of mitochondrial dysfunction, confirm the direct involvement of mitochondria in the violation of the inflammatory response of monocytes revealed in this study as an increased secretion of inflammatory cytokine TNF-α.